SCREENING FOR ANTI-INFLAMMATORY AND ANTI-ALLERGIC ACTIVITY OF BHARANGI {CLERODENDRUM SERRRATUM (LINN.) MOON} IN ANIMALS - N.K.BHANGARE; T.A.PANSARE; B.B.GHONGANE; T.M.NESARI (International Journal of Pharma and Bio Sciences, 2012)
Objectives: The currently available anti-inflammatory and anti-allergic drugs have certain limitations like adverse effects and low efficacy, so there is need to explore the new fields. The root and stem of Bharangi were evaluated for the same using animal models. Methods: Anti-inflammatory action in rats was assessed by Granuloma pouch method. The anti-allergic activity was evaluated by Milk induced Leucocytosis in mice and Bronchial Hyper-reactivity in Guinea Pigs sensitized with egg albumin.(6 groups,n=6) .Results: This study shows that Low Dose (LD) of Bharangi root and High Dose (HD) of stem shows anti-inflammatory (23%) and anti-allergic activity (21%) equivalent to Dexamethasone (21%). But the high dose of Bharangi root has promising anti-inflammatory (44%) and anti-allergic activity (35%). Anti-allergic activity is minimal (8.6%) for LD of stem. Conclusion: This study indicates that Bharangi Root is more effective than Stem and its HD would have useful anti-allergic and anti-inflammatory activity in diseases like asthama; which needs to be further confirmed.